Studies of the constructed rail seat supports - M. Yu. Khvostik; M. A. Starodubtseva (Вестник Научно-исследовательского института железнодорожного транспорта, 2017)
In recent decades, the use of constructed sleepers on the world's railways has been increasing: the United States, the EU countries, Japan and China. Such sleepers, having positive performance qualities of wooden sleepers (good elasticity and dielectric properties, manufacturability during laying and during repair work), do not have negative qualities of wood. The article reviews the US and EU standards for testing sleepers made of constructed materials. The classification of such sleepers is given. Examples of testing of such sleepers by specialists of JSC “VNIIZhT” for the period from 1999 to 2016 are given, including sleepers from modified wood, wooden sleepers with elastomeric coating, composite sleepers from recycled high-density polyethylene with glass-filled polymer. Features of the Russian requirements to the constructed sleepers are considered. Composite rail seat supports are promising in application. Possessing the advantages of wooden sleepers (bars), they have higher wear resistance, lower life cycle costs (recyclable), are more homogeneous and do not rot. Damping properties of composite sleepers contribute to solving the problem of reducing noise and vibration from rolling stock. In addition, their use is one of the ways to reduce the negative impact of rail transport on the environment. With a feasibility study, such sleepers will successfully replace other types of rail seat supports. Spheres of rational application of composite rail seat supports are heaving sections of the railway track, areas with weak soils, turnouts, tracks on bridges, railway tunnels, and underground tracks. Taking into account the tendency to expand the polygon for laying composite sleepers, including railway tracks, metro routes and land transport in the Russian Federation, Kazakhstan and other CIS countries, it is advisable to develop a single interstate standard containing safety requirements and test methods for constructed rail seat supports.